Investigating cortical arousal and cognition in schizophrenia and methamphetamine-induced psychotic disorder: an electroencephalography and cytokine study - Williams, Kimberley Clare (Department of Psychiatry and Mental Health, 2023)
Introduction: Schizophrenia (SCZ) and methamphetamine-induced psychotic disorder (MPD), are psychotic disorders characterized by positive symptoms (e.g., hallucinations and delusions), negative symptoms (e.g., social withdrawal, apathy), and impaired cognitive function. Despite the overlap in the clinical presentation of SCZ and MPD, no studies have compared electroencephalography (EEG) and inflammation across these two conditions. This study aimed to investigate key differences in brain electrical activity on EEG between SCZ and MPD by investigating; (1) relative frequency (alpha, theta, beta and delta) at rest; (2) cognitive performance and relative frequency activity during the continuous performance task (CPT) and cued target detection task (CTD); (3) differences in the P300 event-related potential waveform (ERP), a measure of attention, during the CPT and CTD; (4) cognitive performance and relative frequency and ERP (N170, P300) during the STROOP task, a measure of working memory and executive function; (5) the associations of (neuro) inflammatory markers with relative frequency and the P300 ERP waveform. Methods: 104 South African individuals, between the ages of 20 and 45 years, participated in this study: 69 outpatients (38 with SCZ (8 females/30 males), 31 with MPD (7 females/24 males)), and 35 healthy controls (CON: 15 females/20 males). All participants underwent a Structured Clinical Interview for Diagnostic Systematic Manual-IV (SCID-DSM-IV), with modifications to include changes made in DSM-5. EEG band frequency oscillations were recorded during baseline conditions: resting eyes open and resting eyes closed, and cognitive tasks (CPT, CTD and the Stroop task). Blood was drawn via venepuncture and serum was used for the analysis of cytokines (interleukin (IL) -1β IL-8, IL-10, IL-12p70, tumour necrosis factor-alpha and interferon-gamma (IFN-γ)) concentrations. Statistical analysis included assessment of normality using the Shapiro- Wilk test, with univariate one-way analysis of variance (ANOVA) of parametric data, and multiple independent Kruskal-Wallis ANOVA for non-parametric data (p)